Eliel Machado - Machado, Eliel (Pontifícia Universidade Católica de São Paulo, 2004)
We analyze problems relating to the struggles of some Latin American socialmovements which, in making demands on the state concerning their owninterests, come into conflict with authorities who are undermining bothinternal sovereignty (ie, not attending to popular demands) and externalsovereignty (ie, submitting to the dictates of transnational capital).